Modeling Amazon Deforestation for Policy Purposes - Clive W. J. Granger; Lykke E. Andersen (Institute for Advanced Development Studies (INESAD), 2006)
Brazil has long ago removed most of the perverse government incentives that stimulated massive deforestation in the Amazon in the 70s and 80s, but one highly controversial policy remains: Road building. While data is now abundantly available due to the constant satellite surveillance of the Amazon, the analytical methods typically used to analyze the impact of roads on natural vegetation cover are methodologically weak and not very helpful to guide public policy. This paper discusses the respective weaknesses of typical GIS analysis and typical municipality level regression analysis, and shows what would be needed to construct an ideal model of deforestation processes. It also presents an alternative approach that is much less demanding in terms of modeling and estimation and more useful for policy makers as well.
Keywords: Q56; Q58; 330; Deforestation; Amazon; Brazil; econometric modeling